Ultrastructure of the intercellular protuberances in leaves of Paepalanthus superbus Ruhl. (Eriocaulaceae) - MACHADO,SILVIA RODRIGUES (2000)
Mature leaves of Paepalanthus superbus exhibit intercellular protuberances between the inner periclinal walls of the epidermal and the parenchyma cells surface, as well as on the surface of the parenchyma mesophyll cells. These structures are mostly prominent around the parenchyma cells, forming a gel capsule-like structure. Histochemical tests with ruthenium red indicate the pectic nature of the intercellular deposits, with scattered lipidic inclusions as revealed by sudan IV and sudan black B. Ultrastructural analyses show a fibrillar matrix with scattered fimbriate and tubular structures, and a distinct margin delimited by a dense membrane-like structure. Our results suggest that the protuberances are derived from secretory activity, and are formed after the development of the intercellular spaces. For P. superbus this structure may represent an important cell wall specialisation, related with the adhesion and transport mechanisms between cells.